Sesja III - Astma i POChP w życiu człowiekaAsthma of aging people - Panaszek, Bernard (Przewodnik Lekarza/Guide for GPs Supplement, 2008)
The population of people aged 65 and over has been increasing in developed countries. The prevalence of asthma in aging patients is estimated at between 6.5 and 17%. Asthma is a significant cause of morbidity and mortality in old age; thus death in asthma occurs mostly in elderly patients. Among patients of this group two distinct clinical presentations of asthma have been described: long-standing asthma and late-onset asthma, after 65 years of life. In addition, aging of the respiratory system influences the symptoms of asthma. Asthma that has been presenting for many years may lead to irreversible obstruction in elderly patients. So, the differential diagnosis of asthma is difficult in older adults and asthma is underrecognized and undertreated in this group. Undertreatment is common in the population of elderly asthmatics and this may depend on diagnostic problems.